ELECTRODE COMPOSITION OF REACTIVE BLACK 5 DYE IN AQUEOUS SOLUTION - HASSAN M. TAMOUS (International Journal of Pharma and Bio Sciences, 2014)
High oxygen evolution overpotential and inexpensive Ti/Co3O4/PbO2/(SnO2+Sb2O3) and (Ti/(SnO2+Sb2O3) electrodes were investigated in this work. These electrodes were prepared and used as anodes for removal of Reactive Black 5 (RB5) dye in aqueous solution. In some local cases in Palestine, wastewater color was found to be the only problem in meeting local effluent standards. This investigation reveals that both electrodes can remove the color of these dyes completely. After 10 min, nearly complete degradation of RB5 was achieved (99.2%, and 91.90) using Ti/Co3O4/PbO2/(SnO2+Sb2O3) and (Ti/(SnO2+Sb2O3) electrodes respectively at pH 6.8, current density 30 mA cm-2 and in the presence of NaCl (4 g L-1) at 25 oC. At the same condition the optimal time for COD removal for Ti/Co3O4/PbO2/(SnO2+Sb2O3) and Ti/(SnO2+Sb2O3 electrodes was 7 and 9 hours.